Wavelength Selective Multi‐Material 3D Printing of Soft Active Devices Using Orthogonal Photoreactions. Issue 2 (23rd January 2023) - Rossegger, Elisabeth; Strasser, Jakob; Höller, Rita; Fleisch, Mathias; Berer, Michael; Schlögl, Sandra
Abstract : Inside Cover : In article 2200586, Sandra Schlögl and co‐workers demonstrate that Acrylate functional coumarin monomers are synthetized and cured by wavelength orthogonal photoreactions yielding soft (405 nm) and stiff (365 nm) networks. Advancing from thin films, the dual wavelength 3D printing of soft active devices is demonstrated with locally controlled mechanical and thermal properties using a single vat. The concept is highly versatile and applicable to acrylate and thiol‐acrylate photopolymers.